Strategies to improve postnatal care in Kenya: A qualitative study - Lizeth Roets; Dinah Chelagat; Annemarie Joubert (Elsevier, 2018)
Introduction: Postnatal care is the most neglected aspect of maternal care globally. Midwives, postnatal mothers and their families pay little attention to postnatal care, assuming that physical recovery is always guaranteed when a mother has had a normal pregnancy and childbirth. Unfortunately, preventable complications occurring during this period are considered the major causes of maternal and neonatal morbidity and mortality. The aim of this paper is to describe the strategies that can be implemented to improve postnatal care in Kenya. Methods: A qualitative descriptive study, using a nominal group technique to gather the data was used to identify strategies that can be implemented to improve postnatal care in Kenya. The national and provincial reproductive healthcare coordinators, as the relevant stakeholders, formed the population and unit of analysis. Findings: Thirteen strategies to improve maternal care, specifically postnatal care, were initially listed, of which six were ranked as the highest priorities by participants. Following the steps of the nominal group technique, six of these strategies were eventually considered to be very important. Capacity-building initiatives, quality data management, quality assurance processes, human resource management, supportive supervision, and the coordination of postnatal care services were ranked as priority strategies that needed to be implemented. The operationalisation of the guidelines developed by the Ministry of Health, Kenya, through the identification of strategies, was a unique feature of the study. Recommendation: It is essential that departments of health implement these strategies to improve the health provided to postnatal mothers and their babies. Prècis: Crucial strategies to improve postnatal care are capacity building, data management, quality assurance, human resource management, supportive supervision and coordination. Keywords: Postnatal care, Strategies for healthcare improvement, Nominal Group Technique